Analysis of SISKEUDES Utilization in Realizing Good Governance in Balohli Botomuzoi Village Botomuzoi District Nias Regency - Cianto Waruwu; Fatolosa Hulu; Palindungan Lahagu (Amkop Management Accounting Review (AMAR), 2026)
Transparent and accountable village financial management is one of the important pillars in realizing good governance. This study aims to analyze the utilization of the Village Financial System (SISKEUDES) application in village financial management, the implementation of good governance principles, and SISKEUDES’s contribution in realizing good governance in Balohli Botomuzoi Village, Botomuzoi District, Nias Regency. This research uses a qualitative approach with descriptive methods. Data collection techniques were conducted through in-depth interviews with five key informants consisting of the Village Head, Village Secretary, Village Treasurer, Acting Head of Government Section, and Community Leader, supported by observation and documentation study. The research results show that the utilization of SISKEUDES in Balohli Botomuzoi Village has been implemented in accordance with the provisions of Ministry of Home Affairs Regulation Number 20 of 2018, covering all stages of village financial management from planning to accountability. However, the implementation of good governance principles has not been optimal, particularly in aspects of substantive transparency, horizontal accountability to the community, and community participation in oversight. SISKEUDES’s contribution to realizing good governance is still limited to fulfilling administrative obligations and has not been maximally integrated with good governance values. The main inhibiting factors include limited human resource capacity, minimal information technology infrastructure, and low community understanding of village financial oversight mechanisms. In conclusion, although SISKEUDES has improved village financial administration, strengthening apparatus capacity, providing technological infrastructure, and increasing community literacy are needed so that good governance can be optimally and sustainably realized.